COLLAGEN BIOSTIMULATORS IN FACIAL REJUVENATION TREATMENT - Henriques, Rosania; Felipe Lopez Bempensante, Nicola; Marostica De Freitas, Alessandra; Takeda, Adriana; Brasil Arioli Nieto, Juliana; Bonetti, Elka; Teruo Suguihara, Roberto (Health and Society, 2025)
This study aims to investigate the efficacy and safety of collagen bio-stimulators in facial aesthetic procedures, focusing on promoting skin elasticity and firmness. The justification for this research is based on the increasing demand for minimally invasive treatments that provide satisfactory results in facial rejuvenation. The adopted methodology consists of a literature review, analyzing scientific articles, systematic reviews, and other relevant materials published in the last ten years. The discussion highlights the effectiveness of bio-stimulators, such as calcium hydroxyapatite and poly-L-lactic acid, compared to surgical treatments, as well as the importance of personalizing procedures and combining them with other aesthetic techniques. The conclusion reaffirms that the research question was positively answered and that the specific objectives were achieved, recommending further research to explore new formulations and their implications.